2016
DOI: 10.1177/0020764016651291
|View full text |Cite
|
Sign up to set email alerts
|

Mental health literacy in Hong Kong

Abstract: Background and Aims:The aim of the current study was to investigate Hong Kong

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 33 publications
(36 reference statements)
0
11
0
Order By: Relevance
“…Perhaps more than any other area of MHL, cross-cultural studies are growing fastest. Some compare people from more than one culture (Altweck et al, 2015; Park et al, 2018; Wong et al, 2017), whereas others concentrate on just one country (Lui, Wong, & Furnham, 2016). Some have reviewed all the MHL data arising from one country (Tonsing, 2018).…”
Section: Variations In Mental Health Literacymentioning
confidence: 99%
See 2 more Smart Citations
“…Perhaps more than any other area of MHL, cross-cultural studies are growing fastest. Some compare people from more than one culture (Altweck et al, 2015; Park et al, 2018; Wong et al, 2017), whereas others concentrate on just one country (Lui, Wong, & Furnham, 2016). Some have reviewed all the MHL data arising from one country (Tonsing, 2018).…”
Section: Variations In Mental Health Literacymentioning
confidence: 99%
“…For instance, Kutcher et al (2016) reviewed over 400 articles and were critical of a number of issues: the limited number of interventions reported in the studies, consistent problems with the measurement of MHL by vignettes, and samples often being restricted to students. Many have been critical of vignette techniques (Furnham et al, 2016;Sai & Furnham, 2013). Others have been much more critical of the vagueness of the construct and poor theory development (Spiker & Hammer, 2018).…”
Section: Mental Health Literacymentioning
confidence: 99%
See 1 more Smart Citation
“…A modified version of the vignette-based MHL scale [ 18 ] was used in this study. The scale was adapted based on recent relevant evidence [ 10 , 18 , 19 ] and comprised three MHL subscales: (1) knowledge, which included a recognition of mental disorders and knowledge of help-seeking options [ 18 ]; (2) perceived stigma [ 10 ]; and (3) discrimination, which included preferred social distance [ 19 ]. There were 51 items in the vignette-based MHL scale, with 12 items in the knowledge domain, 24 items in the stigma domain, and 15 items in the discrimination domain (Table 1 ).…”
Section: Methodsmentioning
confidence: 99%
“…There is a strong sense of shame and negative stereotypes about the dangers associated with perceptions of mental illness in Chinese communities [ 9 ]. Previous studies have suggested that Chinese people tend to somaticise the symptoms of depression and thus suppress the emotional components of the disorder [ 10 ]. Rather than acknowledge the psychological distress associated with a mental disorder, Chinese people tend to express it as a physical symptom.…”
Section: Introductionmentioning
confidence: 99%